Application of Local Wisdom-Based Discovery Learning Model to Improve Students' Critical Thinking Skills - Arifa Billa; Beni Setiawan; Mohammad Romadhoni (Jurnal Pemberdayaan Masyarakat, 2025)
Education should produce human resources who have competencies in the 21st century. One of the 21st-century skills students need to have is critical thinking skills. This study aims to analyse three aspects: the improvement of students' critical thinking skills, the implementation of learning, and student responses to the application of the discovery learning model based on local wisdom in the material of separating mixtures. This type of research utilized descriptive-quantitative methods. The subjects of this research were students of grade 8A MTs Negeri 2 Situbondo. There are observation methods, tests, and response questionnaires. The results of this study indicate that the application of the discovery learning model can improve students' critical thinking skills, as indicated by an N-Gain score of 0.73, which meets high criteria. The implementation of learning using this model yielded a percentage result of 91.62% at the first meeting and 95.37% at the second meeting, both in the very good category. Student responses to learning showed very good results, a total percentage of 92% with very high criteria. These findings suggest that the discovery learning model, grounded in local wisdom, effectively enhances students' critical thinking skills, ensures well-implemented learning, and receives positive feedback from students. These results not only support local contextual learning but also contribute to global science education by showing that integrating cultural relevance can enhance critical thinking in diverse classroom settings.